Ações de detecção precoce do câncer de mama realizadas por profissionais da estratégia saúde da família - Costa, Francisca Marta de Lima (2009)
This study is an exploratory descriptive study with a quantitative approach. The objective was to identify the actions for the early detection of breast cancer conducted by the health professionals of the Family Health Strategy in the Trairi region of the State of Rio Grande do Norte, Brazil. The research was conducted in nine municipalities of the region. Data were collected by means of a questionnaire with 52 Family Health Strategy professionals, 30 nurses and 22 physicians, that work in the region. Analysis was conducted using descriptive statistics. The results were organized and discussed in three areas: Knowledge about the early detection of breast cancer; Actions for early detection detection of breast cancer, and Difficulties experienced in the screening actions for breast cancer. The results indicate that these professionals (100%) have knowledge of the signs and symptoms of breast cancer and that the majority (96,2%) conduct screening actions in accordance with the recommendations of the Ministry of Health. However, a considerable number (55,8%) of these professionals encounters difficulties while conducting the screening procedures in his work setting. The difficulties varied from those of a personal nature to those of access to the procedure, such as the unavailability of sufficient quotas of screening exams. We conclude that the majority of health professionals execute the screening actions for breast cancer in their work settings according to the recommendations of the Ministry of Health, even though they encounter difficulties in the conclusion of the mammography and ultrasound exams, essential procedures in the early detection of breast cancer. We understand that these professionals demonstrate knowledge of secondary prevention even though they do not execute all the actions necessary for early detection primarily because they are impeded by the blockage of access to exam quotas. We conclude that, in spite of the difficulties experienced, the procedures for the early detection of breast cancer are being executed by the majority of the Family Health Strategy professionals in the Trairí region, specifically the clinical examination of the breast, orientation of breast self examination, requests for mammography and ultra sound examinations. Measures are needed that can mediate the difficulties, that will permit the realization of secondary prevention procedures with the population at risk in the region. We suggest training and actualization courses on the complete screening process that includes a wide discussion of the new legislation that provides the mammography exam for women over 40 years. We believe that the acquisition of such a work perspective for the early detection of breast cancer, along with knowledge of health vigilance and of breast cancer, will enhance integral health care of women that constitutes an aim of the nurse and the family health team